If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -4 + -3y + 1 = 0 Reorder the terms: -4 + 1 + 6y + -3y = 0 Combine like terms: -4 + 1 = -3 -3 + 6y + -3y = 0 Combine like terms: 6y + -3y = 3y -3 + 3y = 0 Solving -3 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 3y = 0 + 3 3y = 0 + 3 Combine like terms: 0 + 3 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 4(2m+1)=36 | | 2/3n+3=9 | | 14+5x=3(-3x+3)-11 | | 7k+5=4k-19 | | 6n-8=16 | | 2k-4=(-8) | | 3Z+6=15 | | m^2-16m-11=0 | | -8u+6(u+6)=20 | | 6s+34=6+4(2s+4) | | x^2-6x+104=4 | | 256=8(4x+12) | | z+13.53=2.53 | | z-2.53=13.53 | | .47z=5.17 | | 8.25y=-82.5 | | 7x+5y=-9 | | y*-5=-.02 | | 32+7x=x+8(4+6x) | | .75y=-7.5 | | x+5+4x-55+7x-130=180 | | -29=-3x-4(-x+10) | | 16.93+y=26.93 | | 17+m=20 | | m-2=1 | | 8x+5+4x-5+11x+10=180 | | 2(x-3)+5=4y-3(x+y) | | log(x)200=15 | | -4y^2-11y-8= | | -9m=27 | | 3(-(5u+1)-(-4u+3))=5(u+4) | | 4(-7x+13)=-144 |